Assessment of urban development: A composite indicator analysis of the safe city index through the ‘benefit of the doubt’ model - Burgoa, Nadine (2023)
This study employs the ‘benefit of the doubt’ (BOD) weighting model to build a composite indicator to evaluate urban development in 60 cities located around the world for 2021. The results of the empirical application based on the data provided by The Economist (i.e., safe city index) reveal the informative power of the proposed composite indicator, relative to models using equal weight restrictions. Findings indicate that there are significant efficiency differences among the analyzed cities, and that cities follow different strategic pathways when it comes to design urban policies. This suggests that there is much scope for strategic and effective support policy in many cities. The results of the study highlight that an analysis based on the BOD approach may offer useful information to policy makers on what strategic actions may potentially optimize the allocation of local resources and, subsequently, enhance urban development.